Enlighten - Institut Agama Islam Negeri Zawiyah Cot Kala Langsa. Program Studi Bimbingan Konseling Islam; Perkumpulan Ahli Bimbingan dan Konseling Islam (Islamic Guidance and Counseling Department of IAIN Langsa, 2018)
Islamic guidance and counseling. Its scope includes counseling in education, sections include research, assessment, supervision in counseling, Islamic Counseling, health counseling, sexual abuse, violence addition counseling, multi-cultural counseling, crisis intervention, trauma counseling, ITC in counseling, counseling career, spiritual counseling, Islamic marriage and family counseling, Islamic counseling and psychotherapy.
Keywords: Counseling : Religious aspects : Islam : Periodicals; Counseling : Periodicals; Counseling : Indonesia : Periodicals; Counseling : Religious aspects : Islam; Counseling; Indonesia